Sahabat-Sahabat Tuhan Yesus Suatu Renungan Teologi Biblis - Berthold Anton Pareira (Sekolah Tinggi Widya Sasana, 2020)
To know who are the friends of Jesus is very important for every christian because He is “the way, the truth and the life” and “no one comes to the Father except through” Him (Jn 14:6). Friends of Jesus are tax collectors and sinners,infants/simple, John the Baptist, Lazarus our friends and every christian who does His commands.